Radiologic and hormonal evaluation of pituitary abnormalities in patients with Bardet-Biedl syndrome - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2011)
To describe the structural changes in the pituitary gland and accompanying pituitary hormonal problems in patients with Bardet-Biedl syndrome (BBS), 11 patients with BBS (median age: 12.8 years, range: 2.5-17.8 years; four boys and seven girls) have been examined for the anomalies of the pituitary region detected by MRI. Accompanying clinical, biochemical, and hormonal profiles concerning the pituitary function of the patients have also been investigated. We have found a high incidence of pituitary anomalies on MRI (63%) and a considerable percentage of hormonal derangements (45%) accompanying these. Among the structural pituitary abnormalities, tumoral changes (n=2), hypoplastic hypophysis, and/or sella (n=4) and rathke cleft cyst (n=2) were detected, whereas disturbances of the pituitary hormones such as growth hormone deficiency, hyperprolactinemia, hypogonadotrophic hypogonadism, and central precocious puberty accompanied the pituitary anomalies in these patients. Pituitary abnormalities and pituitary hormonal dysfunction are common findings and, therefore, should be included in the diagnostic criteria of BBS. Clin Dysmorphol 20:26-31 (C) 2011 Wolters Kluwer Health | Lippincott Williams & Wilkins.
Keywords: Bardet-Biedl syndrome; MRI; pituitary; SYNDROME PROTEINS; TESTOSTERONE; POPULATION; CRITERIA